Functional movement screen scores in female horse-riders - Edwards, T.; Douglas, J.; Davies, E.; Lewis, V. (11th International Conference International Society for Equitation Science, 2015)
Videographic performance analysis has been found to be effective in the training of other sports, yet limited research has evidenced the most effective feedback techniques for equestrian athletes. The aim of this study was to investigate whether videographic feedback affects positional kinematics of the rider in sitting trot. A sample of riders (n=14, mean age 9.4±1.8 years), were randomly assigned to either the control (verbal feedback only) or intervention (verbal and videographic feedback) group. Each rider rode their own horse in their usual tack and were given individual feedback by a UKCC L2 coach. Participants performed a 15 minute warm up), they were instructed to perform sitting trot once around the perimeter of a 25 x 35m arena on both reins, recorded in the sagittal plane by a 60 Hz Sony SR37 camcorder (used for kinematic analysis) and an iPad (used for visual feedback), 12m from the track 1.5m from the ground. The participants were given their feedback (verbal for control or verbal and video for intervention) and 10 minutes to practise. Riders repeated sitting trot on both reins. The relative angles of the shoulder, hip and knee were measured and analysed on Dartfish 7 software. Tests for difference were analysed using a paired T-Test on SPSS v21. The intervention group reported significant differences (p<0.05) between angles pre-and post-video feedback in hip and knee angles (mean±SD angle; hip left pre=135.1±8.7°, post=145.4±8.6°, hip right pre=135.4±10.7°, post=145.2±7.8°; knee left pre=127.6±7.3°, post=134.3±9.0°, knee right pre=122.4±6°, post=129.60±6.3°). No differences were reported for the shoulder (p>0.05). The control group reported no differences pre-and-post feedback (p>0.05). The control group reported significant asymmetry between left and right angles of the shoulder both pre (left 24.9±4.3°, right 21.1±3.2°, p=0.015) and post (left 26.9±3.1°, right 20.9±3.6°, p=0.009) feedback. The intervention group reported differences between left and right angles of the knee both pre (left 127.6±7.3°, right 122.43±6.0°, p=0.003) and post (left 134.3±9.0°, right 129.6±6.3°, p=0.035) feedback. Verbal feedback combined with videographic analysis reported increased angles of the hip and knee, which has been established as an elite positional trait by prior literature. As a sport where an athlete is often required to self-coach, videoing performance is a technique riders and coaches should consider implementing into their regime more regularly. LP: The riders were given video feedback on an iPad whic indicates that although for scientific analysis a specific camera is required, for visual feedback smartphones and tablets are effective for improving position than when compared to verbal feedback alone. Coaches may wish to consider the use of video feedback within their sessions, or promote riders to send video feedback to their coach when self-coaching.